Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Net Profit Margin pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia 2023-2025 - Mahmud Lewis Ismail; Rio Monoarfa; Ikhlas Ul Aqmal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Net Profit Margin (NPM) in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. The study is motivated by the financial challenges faced by the transportation and logistics sector due to rising operational costs and fluctuations in global oil prices, which require companies to maintain liquidity, capital structure, and profitability simultaneously. This research employs a quantitative approach using multiple linear regression analysis. The population consists of 40 transportation and logistics companies, while the sample was selected through purposive sampling, resulting in 36 companies that met the research criteria. The data used are secondary data obtained from the companies’ financial statements for the 2023–2025 period. The results indicate that the Current Ratio has a significant effect on Net Profit Margin, suggesting that a company’s ability to meet short-term obligations is related to its profitability level. In addition, the Debt to Equity Ratio also affects Net Profit Margin, indicating that the company’s financing structure is associated with its ability to generate net income. Simultaneously, Current Ratio and Debt to Equity Ratio have a significant effect on Net Profit Margin in transportation and logistics companies listed on the IDX. These findings support signaling theory, which states that financial ratios can serve as signals of a company’s condition to external parties in assessing company performance and prospects.